The “Susuka” Application to Improve Sentence-Building Learning for Deaf Students - Maizal Padri; Antoni Tsaputra; Nurhastuti; Elsa Efrina; Rahmahtrisilvia (Jurnal Pedagogi dan Pembelajaran, 2025)
Sentence construction is an essential aspect of language and communication development. However, students with hearing disabilities often struggle to form complete sentence structures due to the limited availability of learning media tailored to their needs and characteristics. This study aims to develop SuSuKa (Susun Susun Kalimat), an educational game-based application designed to support sentence construction skills among students with hearing disabilities. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The participants were five elementary school students with hearing disabilities. The SuSuKa application was validated by two experts, namely an expert in hearing disability education and an instructional media expert, while practicality was assessed by teachers. Effectiveness was measured through pretest and posttest assessments of sentence construction skills. The findings showed that SuSuKa was highly valid (Aiken’s V > 0.90), rated highly practical by teachers (0.908), and effective in enhancing sentence construction skills. The Wilcoxon Signed-Rank Test revealed a significant difference between pretest and posttest results (Z = -2.032, p = 0.042) with a large effect size (r = 0.91). These results indicate that SuSuKa is not only statistically effective but also pedagogically and humanistically relevant, providing interactive visual learning experiences that support more inclusive language learning for students with hearing disabilities.